Human Resource Management Strategy in an Effort to Increase Company Competitive Advantage - Novia Egi Falerian; Eloh Bahiroh (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
Human resources (HR) is one that is very important and even cannot be separated from an organization, both institutions and companies. HR is also the key that determines the development of the company. In essence, HR is in the form of humans employed in an organization as movers, thinkers and planners to achieve the goals of the organization. In fact, the role of HR seems to be forgotten because in general the company / organization is still oriented towards the end result, the final achievement for the organization is profit as a company goal. So it can be concluded that the concept of “competitive advantage” has not become the orientation of thinking of the leaders of organizations and companies, while it should be competitive advantage that becomes the company's achievement, while profit is the result of excellence. In Indonesia, quite a lot of companies were built and indeed mastered certain businesses and triumphed for a generation, but in the end it did not last long because the regeneration of human resources was not prepared from the beginning to maintain excellence in a sustainable manner. This research aims to find out how the strategy, role and training and development of HR in a company so that it can compete with other companies.